COMPARISON OF MOORE'S (POSTERIOR) APPROACH VS. HARDING (LATERAL) APPROACH IN TOTAL HIP ARTHOPLASTY - RAZA , SA; MINHAS , NM; ALI , A; KHAN , SY; FAYYAZ , HA; RAJA , HR; ATIF , ZUR; HAQ , A; ULLAH , S; IQBAL , M (Biological and Clinical Sciences Research Journal, 2023)
The primary objective of this study was to conduct a comparative analysis between Moore's and Harding's approaches for total hip arthroplasty. A randomized controlled trial was undertaken at the esteemed Department of Orthopaedics, Mayo Hospital, Lahore, from 01-06-2020 to 30-06-2022. The study encompassed individuals of both genders, aged 40 years and above, undergoing total hip arthroplasty for various reasons. These participants were divided into two distinct groups: Group A received treatment through the lateral or Harding's approach, while Group B underwent the posterior or Moore's approach. A comprehensive assessment of diverse outcomes was performed. The total cohort for this study consisted of 60 cases, with each Group containing 30 cases. The average age of the participants was 63.57±9.11 years for Group A and 62.79±8.43 years for Group B, revealing no statistically significant difference (p=0.67) between the two groups. The mean duration of the surgical procedure exhibited variance, with Group A recording a time of 77.31±10.91 minutes and Group B with a shorter duration of 64.41±8.19 minutes (p=0.01). Interestingly, the incidence of recurrence displayed a noteworthy contrast between the approaches. The posterior approach yielded a significantly higher recurrence rate, observed in 9 cases (30%), as opposed to the lateral Group, which exhibited recurrence in 3 cases (10%) (p=0.01). Consequently, these findings conclude that the lateral approach boasts a substantial advantage in minimizing recurrence rates. Conversely, the posterior approach achieves a more efficient mean surgical duration. This investigation establishes the superiority of the lateral approach in reducing the recurrence rate while acknowledging the posterior approach's proficiency in achieving a shorter mean surgical duration. This study not only contributes to the advancement of surgical techniques but also provides valuable insights into clinical decision-making in the realm of total hip arthroplasty.